Islamic Boarding Schools and Digital Education: Redefining Roles in the Context of Makassar - Thahir, Mustain; A, Darmawati; Mana, Rivai; Salam, Supardi; Darwis, Arisa (Cita konsultindo, 2025)
Islamic boarding schools (pesantren) have long been central to Indonesia’s educational and cultural landscape, serving as custodians of Islamic learning and community values. However, the rise of digital education has prompted pesantren to reconsider their roles in preparing students for the demands of the 21st century. This study explores how pesantren in Makassar negotiate the integration of digital technologies while preserving their traditional functions. Using a qualitative case study design, data were collected through semi-structured interviews, classroom observations, and document analysis across three pesantren with varying levels of digital readiness. Thematic analysis revealed four key findings: first, pesantren exhibit different levels of digital readiness shaped by institutional resources and leadership commitment; second, teaching practices are gradually shifting toward blended pedagogies where digital tools complement traditional halaqah methods; third, challenges such as infrastructural gaps, digital literacy disparities, and cultural resistance continue to limit adoption; and fourth, pesantren are redefining their identity as hybrid institutions that combine religious tradition with technological innovation. These findings underscore that pesantren in Makassar are not merely adapting to digital transformation but actively reshaping their educational mission. Policy support, teacher training, and community collaboration are essential to ensure inclusive and context-sensitive digital integration within pesantren.